Romantic acts in Portugal - Félix Neto (1997)
Two studies are presented in this paper. In the first, 103 university women between ages 19 and 27 yr. completed an open-ended questionnaire on romantic acts. They were asked to cite specific acts of romance. Among the top three most frequently specified acts were sending or receiving flowers, sharing outdoor leisure activities, and walking. Responses were compared to those of recent studies in which similar information was sought. In Study 2, 133 university women of an average age of 21.2 yr, ranked acts of romance by their importance. Most highly ranked items were related to acts involving physical behavior in contrast with the 1992 study of Tucker.